Analisis Pesan Moral dalam Novel Padang Ilalang di Belakang Rumah Karya N.H Dini - Ade Yayang Latifah; Syahla Syahira; Mona Viddya (Departement of Mathematics Education, 2024)
This research aims to reveal and analyze the moral message in the novel Padang Ilalang di Balang Rumah by N.H. Early. The method used is descriptive qualitative with a pragmatic approach that focuses on the reader. The research results show that this novel contains various important moral messages, including humans' relationships with themselves, each other, the social environment, and God. Moral messages about humans' relationships with themselves include character characteristics such as sensitivity, shyness, alertness, and competitive nature. Human relationships with each other are highlighted through the importance of solidarity and mutual assistance. The social and economic changes resulting from the arrival of Japan which changed the government system illustrate the importance of adaptation in facing social change. The message about the importance of being grateful to God for the sustenance and natural wealth received is also conveyed in this novel.